Bacteriological Safety Assessment of Three Street vended Foods in Owerri , Imo State (P04-141-19) - Francisca, Ezeh (Curr Dev Nutr, 2019)
OBJECTIVES: Street vended foods are common in Nigeria, serving the purposes of supplementing family income and meeting food demand of low income urban dwellers. However these foods can become a vehicle for transmitting food borne pathogens due to poor processing and handling. This study is aimed at accessing the safety with respect to pathogenic bacteria of three foods abacha salad, roasted pork and ukwa (Treculia Africana) commonly vended. in owerri, Imo state.Nigeria METHODS: Twelve samples (four each of Abacha roasted pork and ukwa) were purchased from different vendors in owerri metropolis Imo state pathogenic bacteria were isolated from the food samples by the poor plate method on nutrient, macconkey Eosin metylene blue and salmonella shilgella agar plates and characterized using a combination of cultural/biochemical and 16 sr RNA squencing techniques the antibiotic suceptibility test was performed for each isolate by the disk diffusion method. The plasmid profiles of isolates resistant to four or more antibiotic were determined followed by plasmid suspitibility test to indicate whether resistance is chromosomal or carried on a mobile element. RESULTS: Thirty one isolates comprising seven species (Acinetobacter baumanII, bacllus sp enterobacter sp.E sherichi, coli k lebisella sp kurthia gIbosonoi sp and salmonella sp were obtained. from the food sample "ukwa showed the highest microbial load isolates 98.8 showed the highest resistant against nalidixic and ampicillin multi drug resistance was observed in 11(35.5) of antibiotics except ampicillin and nalidixic acid. CONCLUSIONS: The presence of pathogenes and multi drug resistance isolates in these street foods renders them unsafe for human consumption, food vends and consumers need greater awareness on basic hygienic and good sanitary practices for food handling and appropriate use of antibiotics to for stall severe food borne diseases by antibiotic resistance stains. FUNDING SOURCES: Federal University Of Technology, Owerri.Imo state Owerri.